On the importance of electron–electron and electron–phonon scatterings and energy renormalizations during carrier relaxation in monolayer transition-metal dichalcogenides. (13th July 2022) - Hader, Jörg; Neuhaus, Josefine; Moloney, Jerome V; Koch, Stephan W
Abstract: An ab initio based fully microscopic many-body approach is used to study the carrier relaxation dynamics in monolayer transition-metal dichalcogenides. Bandstructures and wavefunctions as well as phonon energies and coupling matrix elements are calculated using density functional theory. The resulting dipole and Coulomb matrix elements are implemented in the Dirac–Bloch equations to calculate carrier–carrier and carrier–phonon scatterings throughout the whole Brillouin zone (BZ). It is shown that carrier scatterings lead to a relaxation into hot quasi-Fermi distributions on a single femtosecond timescale. Carrier cool down and inter-valley transitions are mediated by phonon scatterings on a picosecond timescale. Strong, density-dependent energy renormalizations are shown to be valley-dependent. For MoTe2, MoSe2 and MoS2 the change of energies with occupation is found to be about 50% stronger in the Σ and Λ side valleys than in the K and K ′ valleys. However, for realistic carrier densities, the materials always maintain their direct bandgap at the K points of the BZ.